The effects of organic and inorganic mulches on the yield and fruit quality of ‘Cripps’ Pink’ apple trees - Van der Merwe, Johannes Dawid Prins (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.